2018
DOI: 10.1002/pros.23689
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of androgen receptor transactivation function by adenovirus type 12 E1A undermines prostate cancer cell survival

Abstract: Ad12 E1A inhibits AR-mediated transcription and suppresses PCa cell survival, suggesting that targeting the AR by E1A12 might have therapeutic potential for treating advanced PCa with heightened AR signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…In vivo studies showed that injection of HAdV-A12 into mouse brain induced cancerous brain tumors [ 73 , 74 ]. Only one study [ 75 ] examined the oncolytic activity of HAdV-A. Li et al [ 75 ] concluded that recombinant HAdV-E1A12 targets androgen receptor (AR)-mediated transcription and kills prostate cancer (PC) cells.…”
Section: Oncolytic Adenoviruses—genetic Modifications To Enhance Onco...mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies showed that injection of HAdV-A12 into mouse brain induced cancerous brain tumors [ 73 , 74 ]. Only one study [ 75 ] examined the oncolytic activity of HAdV-A. Li et al [ 75 ] concluded that recombinant HAdV-E1A12 targets androgen receptor (AR)-mediated transcription and kills prostate cancer (PC) cells.…”
Section: Oncolytic Adenoviruses—genetic Modifications To Enhance Onco...mentioning
confidence: 99%
“…Only one study [ 75 ] examined the oncolytic activity of HAdV-A. Li et al [ 75 ] concluded that recombinant HAdV-E1A12 targets androgen receptor (AR)-mediated transcription and kills prostate cancer (PC) cells.…”
Section: Oncolytic Adenoviruses—genetic Modifications To Enhance Onco...mentioning
confidence: 99%
“…Previous studies have found that adenoviruses can produce at least 50 serotypes. Through the study of various serotypes, it is found that serotype 12E1A inhibits AR-mediated transcription and prostate cancer cell survival, suggesting that E1A12-targeted AR may have a potential therapeutic effect on the treatment of advanced prostate cancer with increased AR (120). In addition to its serotype affecting the development of prostate cancer, adenovirus expressing Fas ligand (FasL) can induce apoptosis in a group of prostate cancer cell lines.…”
Section: Virusmentioning
confidence: 99%